1990
DOI: 10.1530/jrf.0.0900279
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and proportion of inner cell mass of bovine blastocysts fertilized in vitro and in vivo

Abstract: Summary. The morphology and proportion of inner cell mass (ICM) of bovine blastocysts cultured in vitro or in vivo in rabbit oviducts after in-vitro fertilization of in-vitro matured follicular oocytes were compared with those of blastocysts fertilized in vivo by a differential fluorochrome staining technique. The delineation of each ICM cell was improved by the transfer of embryos derived from in-vitro fertilization to a rabbit oviduct although the cell\p=n-\cellcontacts of ICM cells were not as tight as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(108 citation statements)
references
References 15 publications
10
96
1
1
Order By: Relevance
“…The number of cells in day 7 blastocysts was determined by either: (1) counting the Giemsa stained nuclei of fixed embryos spread onto glass slides; or (2) by combining the differential cell counts of the trophectoderm and ICM using procedures as previously described (Iwasaki et al 1990). In vivo embryos were obtained as described above using a total of 20 animals in two separate experiments.…”
Section: Cell Counting Of Blastocyst Embryosmentioning
confidence: 99%
“…The number of cells in day 7 blastocysts was determined by either: (1) counting the Giemsa stained nuclei of fixed embryos spread onto glass slides; or (2) by combining the differential cell counts of the trophectoderm and ICM using procedures as previously described (Iwasaki et al 1990). In vivo embryos were obtained as described above using a total of 20 animals in two separate experiments.…”
Section: Cell Counting Of Blastocyst Embryosmentioning
confidence: 99%
“…Finally, from these results it appears that the viability of in vitro-derived embryos is still lower than for in viw embryos. Morphological, cellular and physiological differ-' ences have been described (Iwasaki et al, 1990; Van Soom and De Kruif, 1992; Leibo and Loskutoff, 1993;Leibo, 1993, 1994) which affect the viability and sensitivity to cooling and freezing. For example, in vitro embryos have a more buoyant density (< 1.2) than in vivo ones (> 1.3).…”
Section: Statisticsmentioning
confidence: 99%
“…Iwasaki et al (1990) found that IVP embryos had a lower ratio of ICM to TE cells, and a less compact ICM compared with both embryos produced entirely in vivo and embryos matured and fertilised in vivo but cultured in vitro. A minimum number of ICM cells is required to obtain a pregnancy and excessive allocation of cells to the TE may lead to pregnancy abnormalities (Van Soom et al 1996;Leese et al 1998).…”
Section: Discussionmentioning
confidence: 90%